PENGUKURAN ENTRASCE SKIN EXPOSURE DAN LAJU PAPARAN RADIASI HAMBUR PADA PEMERIKSAAN KEPALA DENGAN METODE TEGANGAN TINGGI DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Anugrah, Nur Azmi (JFT: Jurnal Fisika dan Terapannya, 2018)
This study aimed to identify the usage method of high voltage tube (kV) with doses and velocity of exposure radiation received by patients during the head checkup and to know the point or safe distance from the radiation sources to the patient and the employee of radiation in the radiology room in Bhayangkara Hospital Makassar . Measuring Entrasce Skin Exposure using multimeter X-Ray Barracuda, and measuring the velocity of exposure radiation using surveymeter at a distance of 1 m, 2 m, and 3 m from the object .The eksposi factor used at voltage tube 70 kV, 80 kV, 90 kV, 100 kV, 110 kV, and the current of tube 200 mA, 160 mA, 100 mA, 50 mA, 20 mA, and time ekspos used 0,250 s. From this research obtained that using of high voltage tube 110 kV produce low Entrasce Skin Exposure 0,590 mGy and using standard voltage tube (kV) 70 kV produce high Entrasce Skin Exposure 4,188 mGy . And measuring the velocity of exposure radiation produce 2500 µSv/h at a distance 1 m, 2200 µSv/h at a distance 2 m, and 1700 µSv/h at a distance 3 m, with high voltage tube at 110 kV. And using voltage tube 70 kV produce low velocity of exposure radiation of 115 µSv/h at a distance 1 m, 72 µSv/h at a distance 2 m, and 7 µSv/h at a distance 3 m. Results showing that the more high voltage tube the more few Entrasce Skin Exposure received to the patients but bigger the velocity of exposure radiation for the employee of radiation and the community and the close distances from sources, higher the rate of exposure radiation, and vice versa . For that reason , point / safe distance for the employee of radiation room and the public should be at a distance 5 m from the radiation sources. Keywords : radiation, Entrasce Skin Exposure , velocity of exposure radiation, high voltage